2014
DOI: 10.1093/cid/ciu722
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Retention and Viral Suppression in the US HIV Safety Net System: HIV Care Continuum in the Ryan White HIV/AIDS Program, 2011

Abstract: The RWHAP provides HIV medical care and support services for more than half a million poor and underinsured individuals living with HIV in the United States. Rates of retention and viral suppression are relatively high compared with other national estimates but demonstrate room for improvement, especially among youth and racial minorities. Additional improvements in retention and viral suppression will contribute to achieving the goals of the National HIV/AIDS Strategy and improve individual and public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 29 publications
0
83
0
Order By: Relevance
“…21,22 Even if 12-month retention had met the NHAS goal, we could not have claimed success as just over half (54%) of patients were continuously retained for the entire 24-month follow-up. Similarly, VS rates declined from 48% at 12 months to 38% at 24 continuous months.…”
Section: Discussionmentioning
confidence: 97%
“…21,22 Even if 12-month retention had met the NHAS goal, we could not have claimed success as just over half (54%) of patients were continuously retained for the entire 24-month follow-up. Similarly, VS rates declined from 48% at 12 months to 38% at 24 continuous months.…”
Section: Discussionmentioning
confidence: 97%
“…In other jurisdictions where such initiatives are not widespread, additional challenges to the uptake and adherence to antiretroviral therapy may be encountered, which may compromise the ability to satisfy this legal test for HIV nondisclosure. Indeed, studies in other North American settings have found that members of marginalized and vulnerable groups, including people who inject drugs, 18-21 ethnic minorities, 22 sex workers 23 and homeless individuals, 24 experience barriers to accessing antiretroviral therapy and achieving sustained viral suppression.…”
Section: Discussionmentioning
confidence: 99%
“…MMP specifically selects persons engaged in HIV medical care and excludes individuals with no medical visits during the sampling period [27]. However, evaluations of similarly engaged HIV-infected populations note comparable results, with retention rates between 82 and 89 % [30, 31]. Historically, patients with mental illness have been less likely to be prescribed ART [3234].…”
Section: Discussionmentioning
confidence: 99%